GERAKAN DAKWAH SULTAN AGUNG (Arti Penting Perubahan Gelar Sultan Agung Terhadap Gerakan Dakwah di Jawa Pada Tahun 1613 M - 1645 M) - Hariyanto Hariyanto (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2018)
The peak of the glory of the Mataram kingdom occurred during the reign of Sultan Agung. He managed to perform da'wah movement to master Central Java, East Java and some areas in West Java. Many strategies of da'wah movement conducted by Sultan Agung. However, the change and the addition of the title by Sultan Agung is one thing that distinguishes the previous Mataram kings. Sultan Agung recorded the changes and the addition of his title ranging from